Study on improving the asynchronous electric drive of ball mills - Shamsutdinov Khusniddin (E3S Web of Conferences, 2024)
In the world, many enterprises in the mining, metallurgical, paint and varnish, chemical industries, as well as in the production of building materials, pay special attention to the problems of starting and accurately stopping ball mills.This article substantiates the expediency of using an adjustable electric motor in grinding mechanisms in electric drives instead of an unregulated asynchronous motor.The problem of facilitating the start-up of ball mills and ensuring accurate stop of the neck of ball mills using the lowest speed is considered. As the review of the literature showed, speed control in electric drives using two-speed motors is a simple, cheap and reliable option.